2008
DOI: 10.1002/prca.200780114
|View full text |Cite
|
Sign up to set email alerts
|

Sera proteomic biomarker profiling in HIV‐1 infected subjects with cognitive impairment

Abstract: HIV-1 infection of the brain commonly leads to cognitive impairments (CI). In its most severe form, HIV-associated dementia is associated with advanced immune suppression and debilitating loss of memory, behavioral, and motor functions. Despite significant research activities, diagnosis remains one of exclusion. Bioimaging, neuropsychological testing, and viral and immune biomarkers serve to support but not define a diagnosis of HIV-1 associated CI. This is timely and required as brain injury triggered by HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 54 publications
6
36
1
Order By: Relevance
“…Differential expression of these proteins were further confirmed in similar analysis performed with SIV infected rhesus macaques 9, 27 . While select proteins in the current study (gelsolin, ceruloplasmin, complement C3, vitronectin, for example) were previously documented being differentially expressed in human samples 18, 25, 26 , the evaluation of these proteins in a broad range of interdisciplinary studies under distinct pathobiologic settings provides further validation for their importance in HIV-1 disease. Here we have expanded such studies by using the iTRAQ platform to quantitatively analyze differentially expressed plasma proteins during the course of SIV infection, with successful validation of selected statistically significant proteins.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Differential expression of these proteins were further confirmed in similar analysis performed with SIV infected rhesus macaques 9, 27 . While select proteins in the current study (gelsolin, ceruloplasmin, complement C3, vitronectin, for example) were previously documented being differentially expressed in human samples 18, 25, 26 , the evaluation of these proteins in a broad range of interdisciplinary studies under distinct pathobiologic settings provides further validation for their importance in HIV-1 disease. Here we have expanded such studies by using the iTRAQ platform to quantitatively analyze differentially expressed plasma proteins during the course of SIV infection, with successful validation of selected statistically significant proteins.…”
Section: Discussionmentioning
confidence: 87%
“…In our previous investigations of plasma samples we used 2DE DIGE platform which resulted in identification of previously not reported differential expression of proteins such as afamin and gelsolin 18, 25, 26 . Differential expression of these proteins were further confirmed in similar analysis performed with SIV infected rhesus macaques 9, 27 .…”
Section: Discussionmentioning
confidence: 99%
“…These changes may remit following cessation of METH use, explaining why we did not observe changes in ceruloplasmin expression in patients after short or long term METH abstinence. In our previous plasma and cerebrospinal fluid (CSF) profiling experiments of HIV-infected individuals we also found ceruloplasmin to be differentially expressed [23], [36], [37]. Interestingly, this protein was down regulated in CSF of subjects with HIV dementia whereas it was up-regulated in plasma, suggesting that the CSF-to-plasma ratio of ceruloplasmin may be an important correlate of HIV-associated neurocognitive impairment.…”
Section: Discussionmentioning
confidence: 75%
“…As in our previous studies, we used quantitative Western blot to validate differentially regulated proteins (Rozek et al, 2008; Wiederin et al, 2009; Wiederin et al, 2010). We initially selected three proteins for validation: gelsolin, vitronectin and ceruloplasmin that were differentially expressed and successfully validated in our previous monkey study of experimental SIV infection (Figure 2 A, C) as well as identified in our current study of the effects of opiate administration on SIV infection (Figure 2 B, D).…”
Section: Resultsmentioning
confidence: 99%